Edukacja menedżerska: geneza i znaczenie w nowoczesnych społeczeństwach - Banaszak, Sławomir (Wydawnictwo Naukowe UAM, 2015)
Managerial education is a very important aspect of modern societies. The paper attempts to show the processes of educating managers as a factor of social and economic development. The author points at the genesis of the education system in Europe and the US as a main issue in the processes of providing qualified staff for the labour market. The article addresses issues of financial effectivity of some MBA programmes and concludes with the approach to the validation of the Polish system of managers’ education (within universities and MBA studies).
Managerial Education: Genesis and Importance in Modern Societies
Keywords: managers; managerialism; MBA studies; management; academic education